Effect of Spacing Regimes on Growth, Yield, and Wood Properties of Tectona grandis at Longuza Forest Plantation, Tanzania. (13th August 2015) - Zahabu, Eliakimu; Raphael, Tumaini; Chamshama, Shabani Athumani Omari; Iddi, Said; Malimbwi, Rogers Ernest
Abstract : This study examined the effects of planting spacing on growth, yield, and wood properties of teak planted at square spacing regimes of 2 m, 3 m, and 4 m at Longuza Forest Plantation, Tanzania. To achieve this, tree, stand, and wood properties were studied at age of 14 years. Results showed that diameter at breast height and total height increased with increasing spacing. Mean annual increment increased significantly with increasing spacing while spacing did not have significant effect on total volume production and basal area. Basic density is also not affected by spacing while heartwood proportion increases as planting spacing increases. All studied wood properties (modulus of rupture, modulus of elasticity, compression strength tangential to grain, and shear tangential to the grain) except cleavage tangential to grain were not significantly affected by increasing spacing. It is recommended to use the spacing of 3 × 3 m, but if thinning can be done before onset of competition at 5 years, the currently used spacing of 2.5 × 2.5 m can still be used. However, the use of a spacing of 4 × 4 m can give at least 50% heartwood at shorter rotation age of 30 years.